La me Profonde. - Kim, Jihea (Tufts Archival Research Center, 2019)
I was born in Korea and grew up in Seoul, Korea. I currently live and work in Boston, Massachusetts. My paintings are intended to provide a sense of calm including abstractions of radiating light as a signifier of the generalized human experience of beauty. I believe there is a general sense of beauty and/or the sublime to be found in the experience of nature.